Prarancangan Pabrik Asam Fenil Asetat dari Benzil Sianida dan Asam Sulfat Kapasitas 3.000 ton/tahun - Prahmawati, Rani, Ir. Nur Hidayati, M.T., Ph.D (2017)
Phenyl acetic acid is a product that used in the fields of pharmacy, beauty, and agriculture. To supply of phenyl acetic acid in the country and still an opportunity to do export, the establishment of phenyl acetic acid plantwould be designed with a capacity of 3.000 tons / year. The raw materials used are benzyl cyanide, sulfuric acid, and water mixture. Planned of phenyl acetic acid plant would be established in Tangerang, Banten on 2020. Phenyl acetic acid production prosessusing a continuous stirred tank reactor to react the benzyl cyanide and sulfuric acid in the solid-liquid phase and isothermal at a temperature of 100°C and a pressure of 1 atm. Conversion reaction is 80%. Filter press is used to separate the reactor product from ammonium hydrogen sulfate. Decanter is used to separate the output of filter press from sulfuric acid and water. The distillation tower is used to purify product of decanter's output with the purity of phenyl acetic acid 99% and 1% benzyl cyanide impurity. Prilling tower is used to crystallize the phenyl acetic acid product by spraying liquid on top. A process support unit includes plant water, steam, compressed air, electricity, and fuel. The plant is also supported by laboratories that control the quality of raw materials, products and plant effluent. The water that needed in a plant would be taken from the river. The water needed for process is as much as 90,4317 kg / hour, for cooling water is as much as 22.063,79 kg / hr, steam providers is as much as 413,9322 kg / h, the compressed airis as much as 109,63 kg / hour, demand for electricity is obtained from PLN and a generator as backup, solar requirement is as much as 0,1019 m³ / h. The selected company line is a Limited Liability Company (PT). The number of employees are 140 persons, devided kind of employees shift and non-shift. Phenyl acetic acid plant with a very low risk of Rp350.821.842.093,98 fixed capital and working capital of Rp 61.144.762.299,49. Profit before tax of Rp 83.965.072.934,51 per year and profit after tax of Rp 58.775.551.054,16 per year. From the calculation, Return On Investment (ROI) before tax is 23,93% and after tax is 16,75%. Pay Out Time (POT) before tax is 2,95 years and 3,74 years after tax. Break Even Point (BEP) is 47,7% and Shut Down Point (SDP) is 21,66%. Discounted Cosh Flow (DCF) is 38,6%. By the calculation result of technical and economic evaluation, the phenyl acetic acid plant with a capacity of 3.000 tons per year is proper to be established.